Arabic Speaking Skills Learning Model Based on the Communicative Approach of Finocchiaro and Brumfits Theory for Students in Pesantren - Muhammad Ibnu Tamam; Abdul Wahab Rosyidi; Nuril Mufidah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Traditional language teaching methods in pesantren, which heavily emphasize grammar and translation, are often ineffective in developing real-world communication skills. The communicative approach offers an alternative by focusing on language use in practical, social contexts to build students' communicative competence, including discourse competence, sociolinguistic abilities, grammatical knowledge, and strategic competence. The aim of this study is to explain the model of a communicative approach on language teaching for speaking skill according to Finocchiaro and Brumfits theory, and to explain procedures that can be applied to students to improve students' language skills. This study uses a qualitative research method with a literature study approach. The results show that communicative approach emphasizes the importance of the ability to communicate effectively in the target language, where learners not only understand the rules of the language theoretically, but can also use the language in real-life situations. Communicative approach is related to students of pesantren who learn a second language, especially Arabic language for their daily activity and its done and can be implemented based on pesantren needs. Thus, the procedures for learning communicative language developed by Finochairo and Brumfit is suitable for a beginner language learning, especially students in pesantren.